Neuro-functional correlates of personality dimensions in Parkinson’s disease - Boussac, Mathilde; Harroch, Estelle; Joineau, Karel; Descamps, Emeline; Brefel-Courbon, Christine (Frontiers in Pharmacology, 2025)
IntroductionAccording to the original model of the Temperament and Character Inventory (TCI), personality dimensions would be related to different neurotransmitters’ systems such as the dopaminergic and the serotoninergic ones.MethodsOur objective was to study associations between functional connectivity and personality in Parkinson’s disease (PD). The data of 29 PD patients were collected (NCT04705207). It included personality evaluation using the TCI, functional connectivity from resting-state functional MRI, and anxio-depressive state from the Hospital Anxiety and Depression scale (HAD). Seed-to-voxels and ROI-to-ROI analyses were done in the CONN toolbox.ResultsSignificant association was found between Novelty Seeking scores and functional connectivity within the nucleus accumbens and one cluster formed of the orbitofrontal cortex. Significant associations were also found between Harm Avoidance scores and functional connectivity within the temporal pole and seven clusters (mainly formed of the post- and pre-central gyri, thalami, parietal lobule, putamen and temporal gyrus). These functional connectivities also correlated with HAD scores.ConclusionIn accordance with the TCI model, Novelty Seeking seems to be related to the dopaminergic system within the nucleus accumbens and orbitofrontal cortex connectivity, implicated in impulsivity. Moreover, Harm Avoidance would be related to the serotoninergic system within the temporal and fronto-thalamo-parietal network connectivity, involved in depressive disorders.Clinical trial registrationclinicaltrials.gov: NCT04705207 (https://clinicaltrials.gov/study/NCT04705207).